The influence of social media and e-WOM on skincare purchasing decisions - Dewi, Puspita; Puspita, Rahista Maya (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
The purpose of this study is to ascertain how Indonesian consumers' decisions to buy skincare products are influenced by the relationship between social media influencers and e-WOM. The study's population is infinite. In order to explain the link between variables, the research strategy employed in this study takes a quantitative approach. A sample of 100 respondents was obtained for the study using the Lemeshow equation as the sampling technique. The statistical technique used in this study is the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. Purchase decisions for skincare products are significantly influenced by social media and e-WOM, according to the research. The findings indicate that interactions and information received through social media as well as positive reviews from other users can influence consumers' level of trust and increase their propensity to make purchases. The implication is that companies in the skincare industry should utilize social media and e-WOM strategies as part of their marketing efforts to attract more consumers.